2023
DOI: 10.1177/17470218231154884
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of familiarity in the context of self-related information processing

Abstract: Humans are inclined to preferentially process self-related content, referred to as the ‘self-bias’. Different paradigms have been used to study this effect. However, not all paradigms included a familiar other condition (but rather an unfamiliar other condition), needed to differentiate self-specific effects from the impact of familiarity. The primary goal of our study was to test the suitability for studying the self-bias of two paradigms that provide robust measures of saliency effects – i.e. the Repetition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 105 publications
(202 reference statements)
1
4
0
Order By: Relevance
“…However, to ensure control over gender-related effects, the gender of close-other faces has to be matched with that of the participant. This selection approach has been consistent with earlier studies (e.g., Tacikowski et al, 2011Tacikowski et al, , 2013Cygan et al, 2014;Nowicka, 2015, 2016;Kotlewska et al, 2017;Nijhof et al, 2018;Cygan et al, 2022;Żochowska et al, 2022Amodeo et al, 2023). Among the participants, 23 individuals opted for a friend, 9 for their sibling, and 3 for their partner as their chosen close-other.…”
Section: Stimulisupporting
confidence: 81%
“…However, to ensure control over gender-related effects, the gender of close-other faces has to be matched with that of the participant. This selection approach has been consistent with earlier studies (e.g., Tacikowski et al, 2011Tacikowski et al, , 2013Cygan et al, 2014;Nowicka, 2015, 2016;Kotlewska et al, 2017;Nijhof et al, 2018;Cygan et al, 2022;Żochowska et al, 2022Amodeo et al, 2023). Among the participants, 23 individuals opted for a friend, 9 for their sibling, and 3 for their partner as their chosen close-other.…”
Section: Stimulisupporting
confidence: 81%
“…Previous research has demonstrated that familiar voices receive special treatment at a cognitive and neurological level (Kanber et al, 2022;Plante-Hébert et al, 2021). Thus, some consider that high familiarity mediates self-biases (Amodeo et al, 2023). Conversely, others argue that cognitive processes involving self-related information are distinct from those related to familiarity (Bortolon & Raffard, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Participants freely selected the close-other based on their subjective high level of closeness and subjective significance to avoid the situation in which a pre-defined close-other might not truly be considered close by the participant. This approach has been employed in numerous previous studies 9 , 10 , 53 , 55 , 56 , 80 , 82 . The only restriction put on the selection of a close-other was that they be of the same sex and have no distinctive facial marks.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of a predefined individual (e.g., a mother, a friend), each participant freely selected their close-other, representing the most significant person in their life at the time of the experiment. This operationalization of a close-other has been utilized in numerous prior studies on the theme of self-prioritization 9 , 10 , 50 , 55 , 56 , 80 82 . Similarly to one’s own face, a close-other’s face is a highly important and salient visual stimulus encountered frequently in everyday life 82 .…”
Section: Introductionmentioning
confidence: 99%